1924
DOI: 10.5962/bhl.title.131982
|View full text |Cite
|
Sign up to set email alerts
|

Gladioli grown by W. F. Shearer : [price list]

Abstract: Bright salmon pink, flaked deep salmon red. Very conspicuous pure white blotches on lower petals. Large flower and tall spikes. Exceptionally attractive. BLOOD SPOT. (Kunderd)-Color dark mahogany with splash of red on lower petals. Vigorous grower.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1968
1968
1991
1991

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Augmentation of the tumoricidal response after the PACC + CA regimen may be related to observations in which CA, in the presence of TAA, exerted a synergistic inhibitory effect on tumor cell replication in tissue culture (5,6), perhaps due to antibody-enhanced phosphorylation and subsequent increased incorporation of the drug into the DNA of cell nuclei. The TAA, measured by radioimmunoassay, are now known to be activated in plasma after perfusion over PACC in vivo and in vitro (3,4).…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…Augmentation of the tumoricidal response after the PACC + CA regimen may be related to observations in which CA, in the presence of TAA, exerted a synergistic inhibitory effect on tumor cell replication in tissue culture (5,6), perhaps due to antibody-enhanced phosphorylation and subsequent increased incorporation of the drug into the DNA of cell nuclei. The TAA, measured by radioimmunoassay, are now known to be activated in plasma after perfusion over PACC in vivo and in vitro (3,4).…”
mentioning
confidence: 97%
“…Indeed, canine immunoglobulin G (IgG) and C'3 bound to tumor cell membranes in situ within 4 hours after extracorporeal perfusion over SAC (3). In separate studies in vitro, TAA were shown to work synergistically with cytosine arabinoside (CA) to inhibit tumor cell replication (5,6). Here we present evidence that a single nontoxic infusion of CA administered to dogs with spontaneous mammary adenocarcinomas after extracorporeal perfusion of plasma over protein A immobilized in collodion charcoal (PACC) results in a necrotizing tumoricidal response that exceeds the reactions observed after extracorporeal perfusion of plasma over PACC or CA infusion alone and the algebraic sum of the reactions to the latter two treatments in the same dogs.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The calculation begins at a time t =0 with a distribution ofplasma density, programme W AZER by Shearer [171,224]. The low"density maximum is caused by the nonlinear force.…”
Section: Approximative Dynamic Casesmentioning
confidence: 99%
“…sequences to the cytoplasm [2,3]. Recent studies show that processing of the pre-nlRNA involves excision of noncoding intervening sequences and splicing together of the coding sequences [4,5].…”
Section: E(sevierlnortlr-i~~l~and Biomedical Pressmentioning
confidence: 99%